2020
DOI: 10.21037/atm-20-3791
|View full text |Cite
|
Sign up to set email alerts
|

Sun’s total arch replacement and stent elephant trunk with modified branch-first technique for patients with Stanford type A aortic dissection

Abstract: Background: Stanford type A aortic dissection (STAAD) is a critical cardiovascular disease, and surgical procedure is the first-choice treatment. The classical surgical procedure still leads to a high mortality rate and neurological complications. In this study, we introduce a new modified Sun's procedure and investigate the association between the branch-first technique and the postoperative outcomes of patients with STAAD.Methods: A total of 108 consecutive patients with STAAD who underwent arch replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Secondly, complex surgical skills are required. For instance, anastomosis of the descending aorta can be difficult because of the deep surgical field ( 14 ). Thirdly, the limbs of the 4-branched arch graft have a tendency to bend or undergo stenosis after closure owing to inappropriate trimming and positioning ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, complex surgical skills are required. For instance, anastomosis of the descending aorta can be difficult because of the deep surgical field ( 14 ). Thirdly, the limbs of the 4-branched arch graft have a tendency to bend or undergo stenosis after closure owing to inappropriate trimming and positioning ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital mortality of this study population was 1.31%, which was lower than recent study (10% reported by Sheng et al [7] and 11.1% reported by Yang et al [35] ). But the mortality was similar to previous reports in our center.…”
Section: Discussionmentioning
confidence: 99%